2006
DOI: 10.1055/s-2005-921501
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Erfahrungen und Ergebnisse über die Anwendung der V.A.C.®-Instill® bei infizierten Hüft- und Kniegelenksprothesen

Abstract: Since September 2005 our patients with acute endoprosthetic infection are treated, next to the normal wound debridement, with a full automatic vacuum drain system (V.A.C. instill system). This therapy unit entail a three step program. Based on the well known vacuum therapy, the new system contains an additional fluid drain and affecting period with an antibiotic or antiseptic instillation therapy. In the last half year we were able to treat five patients with endoprosthetic infection by using this therapy unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Kelm et al reported an infection eradication in 9 out of 10 patients having early infections after total hip or excision arthroplasty by means of the conventional V.A.C.-system at a mean follow-up of 21 months 6. Kirr et al showed good results in 3 cases by using the V.A.C.-Instill ® system in the treatment of early infections after total hip replacement (follow-up not reported) 7. Lehner and Bernd made similar observations with the V.A.C.-Instill ® system in 2 cases at a follow-up of 8 and 22 weeks, respectively 10.…”
Section: Discussionmentioning
confidence: 99%
“…Kelm et al reported an infection eradication in 9 out of 10 patients having early infections after total hip or excision arthroplasty by means of the conventional V.A.C.-system at a mean follow-up of 21 months 6. Kirr et al showed good results in 3 cases by using the V.A.C.-Instill ® system in the treatment of early infections after total hip replacement (follow-up not reported) 7. Lehner and Bernd made similar observations with the V.A.C.-Instill ® system in 2 cases at a follow-up of 8 and 22 weeks, respectively 10.…”
Section: Discussionmentioning
confidence: 99%
“…Lehner and Bernd 10 treated two hip and one knee early periprosthetic infections successfully using intermittent NPWTi. Kirr et al 11 reported the successful treatment of early knee and hip periprosthetic infections with intermittent NPWTi.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent NPWTi is starting to be used successfully to treat early periprosthetic infections of endoprostheses. 10 , 11 However, few articles have reported the outcome of treatment with intermittent NPWTi for late persistent periprosthetic infections of the hip. 12 , 13 In this study, we report two cases who underwent several rounds of radical wound debridement for the treatment of a late persistent periprosthetic infection of the hip.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used in the treatment of knee osteoarthritis, septic arthritis, and temporomandibular joint disorders [35], [36], [37], [38], [39]. It has also been explored to treat PJI using different drugs in the lavage [40], [41], [42], [43], [44]. The continuous lavage can effectively reduce the bacterial load on various surfaces [45] and maintain the concentration of drug in the joint cavity.…”
Section: Discussionmentioning
confidence: 99%